2020
DOI: 10.1016/j.ajogmf.2020.100116
|View full text |Cite
|
Sign up to set email alerts
|

Variations in reported outcomes in studies on vasa previa: a systematic review

Abstract: This systematic review was conducted as part of developing a core outcome set for studies on vasa previa (COVasP), which is being funded by the International Vasa Previa Foundation. R.D. has received speaking honoraria from Ferring Canada for presentations on induction of labor, unrelated to this topic. The other authors report no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 119 publications
(32 reference statements)
0
8
0
1
Order By: Relevance
“…As others have noted, a more uniform reporting of cases will be critical to make further advances in the care of these high-risk pregnancies. 20,21 It is possible that there is limited duplicate reporting of cases. For example, the report of Oyelese et al 22 included cases from the Vasa Previa Foundation, and it is unknown whether any of these cases might have been captured in other case series.…”
Section: Discussionmentioning
confidence: 99%
“…As others have noted, a more uniform reporting of cases will be critical to make further advances in the care of these high-risk pregnancies. 20,21 It is possible that there is limited duplicate reporting of cases. For example, the report of Oyelese et al 22 included cases from the Vasa Previa Foundation, and it is unknown whether any of these cases might have been captured in other case series.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Villani et al demonstrated that reporting of outcomes in VP studies have been limited and highly variable, with most studies including data related to clinical outcomes (eg, fetal heart rate, birth weight, need for transfusion) and very little exploration of outcomes such as maternal and fetal life impact, perception of care, or health resource utilization beyond the immediate peripartum period 23 . Future practice guidelines will benefit from rich and descriptive data surrounding the impacts of institutions' chosen screening protocols, whatever they may be, and even small reports with careful consideration of the factors that can impact decision‐making will be of great value in amassing necessary data.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that a sample of 10 people to be sufficient for this step. After piloting, the survey will be made available online (through links on social media) and widely distributed through identified listservers of relevant organisations, including but not restricted to the Cochrane Pregnancy and Childbirth Group (30 members), the Global Obstetric Network (237 members), Core Outcomes in Women’s and Newborn Health (CrOWN) initiative (77 members), corresponding authors of publications on vasa previa included in a recent systematic review, 23 IVPF, United Kingdom Obstetric Surveillance System ( https://www.npeu.ox.ac.uk/ukoss ), UK Vasa Praevia Raising Awareness Trust ( http://vasapraevia.co.uk ), Australasian Maternity Outcomes Surveillance System ( https://www.amoss.com.au ), Perinatal Society of Australia and New Zealand ( https://www.psanz.com.au ) and Vasa Praevia Support and Awareness Ireland ( https://www.facebook.com/vasapraeviasupportandawarenessIreland ). We will aim to recruit at least 25 individuals from each stakeholder group to ensure an appropriate degree of representation.…”
Section: Methods and Analysismentioning
confidence: 99%